Optical beam deflection sensor: Design and experiments - Sakamoto, João M. S.; Marques, Renan B.; Kitano, Cláudio [UNESP]; Rodrigues, Nicolau A. S.; Riva, Rudimar (Optica Publishing Group, 2017)
In this work, we present a double-pass optical beam deflection sensor and its optical design method. To accomplish that, a mathematical model was proposed and computational simulations were performed, in order to obtain the sensor’s characteristic curves and to analyze its behavior as function of design parameters. The mathematical model was validated by comparison with the characteristic curves acquired experimentally. The sensor was employed to detect acoustic pulses generated by a pulsed laser in a sample surface, in order to show its potential for monitoring applications handling high energy input as laser welding or laser ablation.